PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CSR) PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 BURSA EFEK INDONESIA (BEI) - Agustya Kurratul Aini (KINERJA, 2015)
The purpose of the research is to find out the Effect of Company characteristics un the disclosure of Corporate Social Responsibility (CSR) on Company Listed on Indonesian Business Exchange LQ45. The variable of the research is public share ownership, leverage which is represented by debt equity ratio, liquidity which is presented by current ratio, Profitability which is represented by return on equity and company growth which is calculated its effect to CSR disclosure using Disclosure scoring. The method that is used is quantitative type of data, Data collecting method used is Documentation Method. The current Data is analyzed using Multiple Linear Regression Analysis. Descriptive Statistics, Classic Statistic Test, and T Test. Selection of data is used Purposive Sampling and was concluded 15 companies that fulfilled the research criteria and were collected 90 research data for 6 years. The result of the research showed that only debt to equity  and return on equity that are affecting the disclosure of Corporate Social Responsibility (CSR), while Public Share Ownership, current ratio and company growth were affecting negatively on Corporate Social Responsibility (CSR) to the companies listed on Indonesian Business Exchange LQ45 Index. Key words:  Public Share ownership,  Leverage,  Liquidity,  Profitability, Company Growth, Corporate Social Responsibility disclosure.